2016
DOI: 10.3390/ijms17111816
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Pathway of Argon-Mediated Neuroprotection

Abstract: The noble gas argon has attracted increasing attention in recent years, especially because of its neuroprotective properties. In a variety of models, ranging from oxygen-glucose deprivation in cell culture to complex models of mid-cerebral artery occlusion, subarachnoid hemorrhage or retinal ischemia-reperfusion injury in animals, argon administration after individual injury demonstrated favorable effects, particularly increased cell survival and even improved neuronal function. As an inert molecule, argon did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…These factors influence or even interrupt neuronal apoptosis, mitochondrial dysfunction and excitoxicity. Systematic reviews by Hoellig [98], Ulbrich [99] and Nespoli [100] have provided detailed information about the molecular pathways of neuroprotection mediated by argon ( Table 2).…”
Section: Neuroprotection By Argonmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors influence or even interrupt neuronal apoptosis, mitochondrial dysfunction and excitoxicity. Systematic reviews by Hoellig [98], Ulbrich [99] and Nespoli [100] have provided detailed information about the molecular pathways of neuroprotection mediated by argon ( Table 2).…”
Section: Neuroprotection By Argonmentioning
confidence: 99%
“…Fahlenkamp et al showed that argon reduces LPS-induced inflammation in microglia cell cultures [102]. Fore a deeper mechanistic understanding of neuroprotection by argon models of apoptosis in human neuroblastoma cells and ischaemia reperfusion were established by Ulbrich et al [99,107,116]. Ulbrich et al identified the inhibition of Toll-like receptors (TLR2/TLR4) and the activation of the NF-κB pathway by argon as relevant regarding the reduction in microglial inflammation.…”
Section: Neuroprotection By Argonmentioning
confidence: 99%
“…In addition, HO‐1 protein combined with protein transduction domains significantly attenuated cerebral vasospasm when injected into the cerebral arteries of rats . The therapeutic potential of HO‐1 inducers, including nicaraven, argon, carnosol, ebselen and CGS26393, has also been revealed . Additionally, nicaraven is known to cause minute side effects during treatment …”
Section: The Pathophysiology Of Sahmentioning
confidence: 99%
“…Ar has a full electron valence shell which avoids covalent binding with other elements; therefore, it is usually considered a nonreactive chemical gas, as known by its Greek name “αργός,” meaning “inert.”[4] Although labeled as a “biologically” inert gas, recent evidence suggest that the drug can have significant effects. Narcotic effects have been described in divers since 1939 and further confirmed by other studies.…”
Section: Introductionmentioning
confidence: 99%